The plasticity of pancreatic cancer stem cells: implications in therapeutic resistance - Kalyani Patil (2679424) (2022)
The ever-growing perception of cancer stem cells (CSCs) as a plastic state rather than a hardwired defined entity has evolved our understanding of the functional and biological plasticity of these elusive components in malignancies. Pancreatic cancer (PC), based on its biological features and clinical evolution, is a prototypical example of a CSC-driven disease. Since the discovery of pancreatic CSCs (PCSCs) in 2007, evidence has unraveled their control over many facets of the natural history of PC, including primary tumor growth, metastatic progression, disease recurrence, and acquired drug resistance. Consequently, the current near-ubiquitous treatment regimens for PC using aggressive cytotoxic agents, aimed at ‘‘tumor debulking’’ rather than eradication of CSCs, have proven ineffective in providing clinically convincing improvements in patients with this dreadful disease. Herein, we review the key hallmarks as well as the intrinsic and extrinsic resistance mechanisms of CSCs that mediate treatment failure in PC and enlist the potential CSC-targeting ‘natural agents’ that are gaining popularity in recent years. A better understanding of the molecular and functional landscape of PCSC-intrinsic evasion of chemotherapeutic drugs offers a facile opportunity for treating PC, an intractable cancer with a grim prognosis and in dire need of effective therapeutic advances. Other Information Published in: Cancer and Metastasis Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10555-021-09979-x